(untitled) (UNED Research Journal, 2020)
Introduction: Teleworking was introduced in the 1970s as a result of the oil crisis and in response to the need for continuing economic activities. Decades later, advances in technology allowed the introduction of this modality globally. Many studies have shown that the benefits for organizations and employees are multiple; these include the increase in job satisfaction and a decrease in stress. Organizations have taken an active role in its implementation because satisfied and less stressed employees are more productive. Objective: Testing the hypotheses that, a) teleworkers are more satisfied, b) teleworkers perceive less stress. Methods: We surveyed 240 teleworkers and 224 presential workers. Results: Teleworkers have greater satisfaction and less stress. Conclusion: Teleworking is, in this institution, a satisfactory option to presential work regarding levels of satisfaction and stress.